Impacts of Local Dimming Algorithms on the Halo Effect in LCD With Local Dimming Mini-LED Backlight - Shuai-Shuai Zhou; Han Gao; Yu-Jiao Ruan; Jian-Bang Zhuang; Yi-Jun Lu; Zhong Chen; Wei-Jie Guo (IEEE Photonics Journal)
The local dimming mini-LED backlight has become one of the most important technologies for liquid crystal display (LCD), facilitating the improvement on high dynamic range (HDR) and power saving. The halo effect still limits the performance of LCDs employing mini-LED backlight. The impact of the number of local dimming zones on the contrast ratio has been investigated. The halo effect has also been investigated under four typical local dimming algorithms and different local dimming zones. It has been experimentally demonstrated that the halo area gradually shrinks with increasing the number of local dimming zones, contributing to the improvement on the HDR of LCD.